Prediction of subclinical left ventricular dysfunction by speckle-tracking echocardiography in patients with anti-neutrophil cytoplasmic antibody--associated vasculitis - Tuba Nur İzgi,; Dilek Barutcu Ataş,; Halil Ataş,; Dursun Akaslan,; Can Ilgın,; Arzu Velioğlu,; Hakkı Arıkan,; Fatma Alıbaz-Öner,; Haner Direskeneli,; Serhan Tuğlular,; Ebru Aşıcıoğlu, (Archives of Rheumatology, 2022)
Objectives: This study aims to evaluate left ventricular functions using speckle-tracking echocardiography (STE) in patients with anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). Patients and methods: Between June 2018 and July 2019, a total of 31 AAV patients (17 males, 14 females; median age: 53 years; range, 47 to 62 years) and 21 healthy controls (11 males, 10 females; median age: 56 years; range, 46 to 60 years) were included in the study. Clinical and biochemical characteristics of all participants were recorded. All participants underwent conventional and two-dimensional STE. The receiver operating characteristic (ROC) curve analysis was performed to determine the cut-off value of serum N-terminal prohormone of brain natriuretic peptide (NT-pro-BNP) that predicted subclinical left ventricular dysfunction. The Spearman correlation analysis was used to determine the correlation between left ventricular global longitudinal strain (LV-GLS) and NT-pro-BNP. Results: The LV-GLS was lower in AAV patients (19.3% vs. 21.7%, respectively; p=0.014). NT-pro-BNP was negatively correlated with LV-GLS (p=0.005, r=0.401). Conclusion: Subclinical left ventricular dysfunction can be detected by STE in patients with AAV who have free of clinically overt cardiovascular disease. The LV-GLS is negatively correlated with serum NT-pro-BNP levels.